Persistent Hypoglycemia in Patient with Hodgkin’s Disease - Harold Cinco Lim; Lubna Bashir Munshi; David Sharon (Case Reports in Oncological Medicine)
Hypoglycemia is a rare complication of Hodgkin’s disease. Several explanations have been postulated but the exact pathophysiology is not well understood. We are presenting a case of newly diagnosed Stage IV Hodgkin’s disease that developed persistent and recurrent hypoglycemia despite giving glucagon, repeated 50% dextrose, and D5 and D10 continuous infusion. Hypoglycemia workup showed the C-peptide level to be low. Patient was suspected of having hypoglycemia related to lymphoma and was given a trial of prednisone which resolved the hypoglycemic episodes and made the patient euglycemic for the rest of his hospital stay. The presence of a substance that mimicked the effects of insulin was highly suspected. Several case reports strengthen the hypothesis of an insulin-like growth factor or antibodies secreted by the cancer cells causing hypoglycemia in Hodgkin’s disease but none of them have been confirmed. Further investigation is warranted to more clearly define the pathophysiology of persistent hypoglycemia in patients with Hodgkin’s disease.